The Effect of Using Digital Interactive Fiction on the Students’ Reading Comprehension Achievement at SMPN 10 Metro - Intan Trine Chodija; Harits Setyawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Conventional way of teaching may influence the students’ results in reading comprehension. Based on the observation in SMPN 10 Metro, the students still had difficulty in comprehending the reading text. This research has aim to find out whether there is a significant difference of students’ reading comprehension after being taught using digital Interactive Fiction. The researcher applied a quantitative research method using a true experimental design, specifically the control group pretest-posttest design. The research was conducted at SMPN 10 Metro in six meetings including pretest, treatment for three sessions, and posttest. The researcher took two classes as the sample randomly using lottery as experimental class and control class. The finding shows that the use of Digital Interactive Fiction had a significant effect on students' reading comprehension. It can be seen from the significance value (0.002) which is lower than 0.05. It can be concluded that it is an effective instructional tool for improving students’ reading comprehension achievement. Further studies can explore digital interactive fiction on different language skills such as vocabulary acquisition.